JURIDICAL ANALYSIS OF MINIMUM CRIMINAL IMPOSITIONS FOR PERSONS OF CORRUPTION CRIMINAL ACTS (STUDY OF DECISION NUMBER 43/Pid.Sus-TPK/2022/PN.Mdn) - Ricky Pratama Ginting; Sumarno; T. Riza Zarzani (CV. RADJA PUBLIKA, 2024)
The crime of corruption is a serious crime and must be eradicated in the Unitary State of the Republic of Indonesia, because it can harm the country. In terms of preventing and eradicating corruption, Indonesia has regulated it in Law number 20 of 2001 as an amendment to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. In this research, there are 3 discussions that will be explained in this research, namelyWhat is the role of judges in applying minimum criminal sanctions for perpetrators of criminal acts of corruption according to the provisions of the law, what are the basic considerations of judges in imposing sentences below the minimum threat for perpetrators of criminal acts of corruption and what is the legal basis for the judge's rationale for imposing criminal sanctions below the minimum for criminal acts of corruption? , in accordance with the provisions of Law Number 20 of 2001regarding changes to Law Number 31 of 1999 concerning the Eradication of Corruption Crimesin accordance with the provisions of Article 2 Paragraph (1) Every person who unlawfully commits an act of enriching himself or another person or a corporation which can harm state finances or the state economy, shall be punished with life imprisonment or a minimum imprisonment of 4 (four) years. and a maximum of 20 (twenty) years and a fine of at least IDR 200,000,000.00 (two hundred million rupiah) and a maximum of IDR 1,000,000,000.00 (one billion rupiah). However, in the case of this research, the judge decided the case was below the minimum sentence.